2022
DOI: 10.1609/aaai.v36i3.20271
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Domain Empirical Risk Minimization for Unbiased Long-Tailed Classification

Abstract: We address the overlooked unbiasedness in existing long-tailed classification methods: we find that their overall improvement is mostly attributed to the biased preference of "tail" over "head", as the test distribution is assumed to be balanced; however, when the test is as imbalanced as the long-tailed training data---let the test respect Zipf's law of nature---the "tail" bias is no longer beneficial overall because it hurts the "head" majorities. In this paper, we propose Cross-Domain Empirical Risk Minimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…During the survey, 9389 women aged 15-49 years in all selected households and 4280 men aged 15-59 years in half of the selected households for women were successfully interviewed. For women with multiple births, we consider the data for the most recent pregnancy with the view of minimising recall bias[13]. Women who had not given birth in the last 5 years prior to the survey and women who had not consulted a health care provider were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the survey, 9389 women aged 15-49 years in all selected households and 4280 men aged 15-59 years in half of the selected households for women were successfully interviewed. For women with multiple births, we consider the data for the most recent pregnancy with the view of minimising recall bias[13]. Women who had not given birth in the last 5 years prior to the survey and women who had not consulted a health care provider were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…Burundi has currently 18 provinces grouped into 5 health regions (Bujumbura-Mairie, West, South, North and Centre-East).The new province of Rumonge (which was a commune of the province of Bururi) is the result of the merger between three former communes of Bururi (Rumonge, Buyengero and Burambi) and two former communes of Bujumbura-Rural (Bugarama and Muhuta). During the survey, 9389 women aged 15-49 years in all selected households and 4280 men aged 15-59 years in half of the selected households for women were successfully interviewed.For women with multiple births, we consider the data for the most recent pregnancy with the view of minimising recall bias [13] .Women who had not given birth in the last 5 years prior to the survey and women who had not consulted a health care provider were excluded from the study.Therefore, the study sample size consists of 5063 Burundian women aged 15-49 years who reported at least one live birth in the five years preceding the survey.The figure 1 below shows ,at national level , the clusters distribution according to place of residence. The red dots are urban's clusters and the green dots are rural's clusters.…”
Section: Population and Sampling Proceduresmentioning
confidence: 99%
“…During the survey, 9389 women aged 15-49 years in all selected households and 4280 men aged 15-59 years in half of the selected households for women were successfully interviewed. For women with multiple births, we consider the data for the most recent pregnancy with the view of minimising recall bias [17]. Women who had not given birth in the last 5 years prior to the survey and women who had not consulted a health care provider were excluded from the study.…”
Section: Population and Sampling Proceduresmentioning
confidence: 99%
“…NIL focuses on the individual supervised learning for each expert, while NBOD facilitates knowledge transfer among multiple experts. Lastly, xERM [64] aims to develop an unbiased, test-agnostic model for long-tailed classification. Grounded in causal theory, xERM seeks to mitigate bias by minimizing cross-domain empirical risk.…”
Section: Related Workmentioning
confidence: 99%